CircNRIP1 Encapsulated by Bone Marrow Mesenchymal Stem Cell–Derived Extracellular Vesicles Aggravates Osteosarcoma by Modulating the miR-532-3p/AKT3/PI3K/AKT Axis - Shi, Zuowei; Wang, Kaifu; Xing, Yufei; Yang, Xuefeng (Frontiers in Oncology, 2021)
Emerging evidence indicates that extracellular vesicle (EV)-encapsulated circRNAs have the potential diagnostic and prognostic values for malignancies. However, the role of circNRIP1 in osteosarcoma remains unclear. We herein investigated the therapeutic potential of circNRIP1 delivered by bone marrow mesenchymal stem cell-derived EVs (BMSC-EVs) in osteosarcoma. The expression of circNRIP1 was examined in the clinical tissue samples of osteosarcoma patients, after which the downstream genes of circNRIP1 were bioinformatically predicted. Gain- and loss-of function assays were then performed in osteosarcoma cells with manipulation of circNRIP1 and miR-532-3p expression. EVs isolated from BMSCs were characterized and co-cultured with osteosarcoma cells to examine their effects on cell phenotypes, as reflected by CCK-8 and Transwell assays. Further, a mouse model of tumor xenografts was established for in vivo substantiation. circNRIP1 was upregulated in osteosarcoma tissues and cells. Overexpression of circNRIP1 promoted the proliferative, migratory, and invasive potential of osteosarcoma cells. Co-culture data showed that BMSC-EVs could transfer circNRIP1 into osteosarcoma cells where it competitively bound to miR-532-3p and weakened miR-532-3p’s binding ability to AKT3. By this mechanism, the PI3K/AKT signaling pathway was activated and the malignant characteristics of osteosarcoma cells were stimulated. In vivo experimental results unveiled that circNRIP1-overexpressing BMSC-EVs in nude mice resulted in enhanced tumor growth. In conclusion, the BMSC-EV-enclosed circNRIP1 revealed a new molecular mechanism in the pathogenesis of osteosarcoma, which might provide a novel therapeutic target for osteosarcoma.